RECYCLING FALLEN LEAVES IN THE CITY OF TASHKENT: ECOLOGICAL AND ECONOMIC ASPECTS - Islamovich, Kushnazarov Pulat; Khamitovna , Bekmukhamedova Munisa (Journal of Geography, Regional Planning and Development, 2025)
Objective: This study explores the ecological and economic implications of fallen leaf recycling in Tashkent, a major urban center in Central Asia with over 254 million trees. The research aims to identify sustainable waste management practices tailored to the city's environmental context. Method: A descriptive-analytical approach was employed, involving estimations of leaf volume, literature review of recycling technologies, and evaluation of potential ecological and economic benefits. Calculations were made to determine the annual volume of fallen leaves, and technological alternatives such as composting, biogas plants, and mulching were assessed. Results: Findings indicate that approximately 254 billion leaves fall annually in Tashkent, creating a significant waste management challenge. Composting emerged as the most feasible solution due to its cost-effectiveness and environmental benefits. Biogas production offers energy potential but requires substantial investment, while mulching presents a low-cost alternative for urban landscaping. Novelty: The article provides a localized, data-driven framework for urban organic waste recycling in Central Asia, highlighting specific environmental and infrastructural constraints in Tashkent. It also integrates ecological impact analysis with economic feasibility, offering a comprehensive model for similar urban ecosystems.